SYNTHESIS AND CHARACTERIZATION OF C-HEXYL CALIX[4]RESORCINARENA FROM RESORCINOL-HEPTANAL CONDENSATION - Handayani, Desi Suci; Almaqqomul Amin, Zainal Arifin; Kusumaningsih, Triana; Masykur, Abu (Alchemy Jurnal Penelitian Kimia, 2014)
Synthesis of C-hexyl calix[4]resorcinarene through condensation reaction between resorcinol and heptanal with HCl catalyst has been investigated. Synthesis conducted by the ratio of resorcinol: heptanal (1:1) using reflux for 6 hours in ethanol. Structural analysis of the product was done by FTIR and 1H-NMR spectroscopy, while the characterization was done by determining melting point. The product was golden brown powder with a yield 99.43% and melting point more than 300 °C. Structural analysis with FTIR and 1H-NMR known vibration and signals characteristic of calix[4]resorcinarena group,the vibrations of the CH bridge. Vibration of CH bridge appearance at wave number 1445 cm-1 and 1456 cm-1, while signal of CH bridge appearance at chemical shifts from 4.17 to 4.21 ppm.